The prototype of decision support system in condition infant detection with Fuzzy Tsukamoto - Agung Setiawan; Budi Yanto; Kiki Yasdomi (International Journal of Health Science and Technology, 2019)
The baby’s condition is a condition that is vulnerable to environmental changes, especially weather changes. Knowledge of a mother in maintaining the health of baby also should be considered, especially in terms of nutritional intake. A healthy baby's condition affects the baby's growth and development. The development of a decision support system should be preceded by collecting and analyzing the data according to need. In this study, the variables were baby feeding items, namely Body Temperature (37.70c), Fuss (2.4), Restless (4.5), frequent bowel movements (3.7), watery bowel movements  (5.6), Bloating (3.5), Nausea (3.7), vomiting (3.2) , Stomachache (2.7) and Itchy Skin (2.8). The results of the calculations will result in defoliation as follows: Measles (1:48), septic (1:48), diarrhea (1:48), ISPA (7:36), enteritis (0.77), Miliary (1:48), OMP (1:48) and varicella (1:48). The range of fuzzy values ranges from 0 to 1, indicating the baby has enteritis or stomach problems. The calculation of defuzification obtained result of 8.1, so the condition of the baby is very sick and should be handled immediately by bringing to the medical personnel.